President Theodore Roosevelt - McKay, Sindy (San Anselmo, CA : Treasure Bay, 2006)
Describes the life of 26th President Theodore Roosevelt and his accomplishments.
Keywords: Roosevelt, Theodore, -- 1858-1919 -- Juvenile literature; Roosevelt, Theodore, -- 1858-1919.; Presidents -- United States -- Biography -- Juvenile literature; Presidents